The lower airway microbiota in early cystic fibrosis lung disease: a longitudinal analysis - Frayman, Katherine B; Armstrong, David S; Carzino, Rosemary; Ferkol, Thomas W; Grimwood, Keith; Storch, Gregory A; Teo, Shu Mei; Wylie, Kristine M; Ranganathan, Sarath C (Thorax, 2017)
RationaleIn infants and young children with cystic fibrosis, lower airway infection and inflammation are associated with adverse respiratory outcomes. However, the role of lower airway microbiota in the pathogenesis of early cystic fibrosis lung disease remains uncertain.ObjectivesTo assess the development of the lower airway microbiota over time in infants and young children with cystic fibrosis, and to explore its association with airway inflammation and pulmonary function at age 6 years.MethodsSerial, semi-annual bronchoscopies and bronchoalveolar lavage (BAL) procedures were performed in infants newly diagnosed with cystic fibrosis following newborn screening. Quantitative microbiological cultures and inflammatory marker (interleukin 8 and neutrophil elastase) measurements were undertaken contemporaneously. 16S ribosomal RNA gene sequencing was conducted on stored BAL samples. Spirometry results recorded at 6 years of age were extracted from medical records.Measurements and main resultsNinety-five BAL samples provided 16S ribosomal RNA gene data. These were collected from 48 subjects aged 1.2–78.3 months, including longitudinal samples from 27 subjects and 13 before age 6 months. The lower airway microbiota varied, but diversity decreased with advancing age. Detection of recognised cystic fibrosis bacterial pathogens was associated with reduced microbial diversity and greater lower airway inflammation. There was no association between the lower airway microbiota and pulmonary function at age 6 years.ConclusionsIn infants with cystic fibrosis, the lower airway microbiota is dynamic. Dominance of the microbiota by recognised cystic fibrosis bacterial pathogens is associated with increased lower airway inflammation, however early microbial diversity is not associated with pulmonary function at 6 years of age.